2008
DOI: 10.1177/0272989x08315246
|View full text |Cite
|
Sign up to set email alerts
|

A Test of Numeric Formats for Communicating Risk Probabilities

Abstract: Percentage and frequency formats facilitate performance of simple operations on risk probabilities compared with the 1-in-n format, which should usually be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
99
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(103 citation statements)
references
References 17 publications
3
99
0
Order By: Relevance
“…7 Further, recent empirical and theoretical work suggests that the use of frequency formats alone is not sufficient to improve reasoning (Reyna & Brainerd, 2008; see also Cuite, Weinstein, Emmons, & Colditz, 2008). In perhaps the most direct test of this issue, Sloman et al (2003) tested the frequency explanation against the nested-sets hypothesis, which states that any manipulation that leads to a correct representation of set structure causes improved performance.…”
Section: Frequency Versus Probability Formatsmentioning
confidence: 99%
“…7 Further, recent empirical and theoretical work suggests that the use of frequency formats alone is not sufficient to improve reasoning (Reyna & Brainerd, 2008; see also Cuite, Weinstein, Emmons, & Colditz, 2008). In perhaps the most direct test of this issue, Sloman et al (2003) tested the frequency explanation against the nested-sets hypothesis, which states that any manipulation that leads to a correct representation of set structure causes improved performance.…”
Section: Frequency Versus Probability Formatsmentioning
confidence: 99%
“…3 More recently, Cuite and coauthors showed that people presented with statistics using the 1-in-X format had significantly greater difficulty doing basic mathematical operations (e.g., doubling the risk) than those presented with other formats. 4 Use of 1-in-X formats is not universal, however. Many health communications use what Pighin and colleagues call N-in-X*N formats that convert the ratio to have round number denominators (e.g., 100, 1000, or 10 000).…”
mentioning
confidence: 99%
“…Participants may have answered differently if directly asked to give their estimated lifetime risk as a percentage. Additionally, there is data to suggest that natural frequency may be a more accurate way to elicit numeric information, however this theory could not be assessed using the data available from this study [40,41].…”
Section: Limitationsmentioning
confidence: 86%